The role of university-industry collaboration in the development of a knowledge economy: case study of universities in the United Arab Emirates. (2015) - Bhayani, Ali
Countries around the globe are emphasising the development of a knowledge economy to drive growth by encouraging universities to be entrepreneurial. Towards this end, universities in Europe and the USA have pursued university-industry collaboration. This paper presents empirical results from case studies of five United Arab Emirates (UAE) universities to identify underlying drivers and the current state of university-industry relations using in-depth, qualitative and multiple case studies to assess the relevance of university-industry relationships and the underlying barriers and opportunities. UAE universities possess some inherent qualities necessary for university-industry collaboration. These include steerage and concern for economic surplus as well as operating in a performance driven environment which allows quick response to a dynamic external environment and capitalises on opportunities. However, there are some areas that require further development such as: encouraging a culture of innovation, the provision of incentives to take risks and, targeted support from the state.